(untitled) - Bean, Michael J. (Westport, Connecticut, 1997)
This book, the third edition of "The Evolution of National Wildlife Law" thoroughly revises and updates the earlier edition in light of current legal perspectives on the conservation of wildlife and biological diversity; monumental achievement that will serve lawmakers, administrators, educators, conservationists, and scholars for years to come
Keywords: Wildlife conservation,Bảo vệ động vật hoang dã; Law and legislation,Luật và pháp chế; United States,Hoa Kỳ